IMPLEMENTATION OF SCHOOL HEADMASTER’S STRATEGIC MANAGEMENT IN THE EFFORT ON INCREASING THE QUALITY OF EDUCATION AT SENIOR HIGH SCHOOL (SMA) OF UISU MEDAN - Nila Safina (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This research aims to know the effort which is done by principal of school increasing education quality and the implementation of management strategic in SMA UISU Medan. This research used qualitative descriptive method, by using observation technique, interview, and documentation study. Key informant in this research is the principal of a school, and supported by another up to date informational which is needed to this research. Technique of processing data has some steps. First, data which is collected must be identified and classified, the analyzed and it is examined the validity by using triangulation, next each founding from the result analysis is correlated one each other to build one logic arrangement aspect which is applied in SMA UISU Medan. Based on this research, it is found some things: first the effort which is done by principal of a school increasing the education quality in SMA UISU Medan is by formulated strategic management thought make the following program: School review, Banch marking, Quality assurance and Quality control. Second, the application of principal of a school strategic management in the effort to increase education quality in SMA UISU Medan very depend on: (1) Education structure organization, (2) Formulation Ursion, Mission, aim and target of school, (3) State organization strategy, (4) Implementation school organization strategy and (5) Do SWOT analysis. Based on the data found, the writer suggest. Firstly, in the activity of increasing education quality, it is a must that all program quality increasing which has been formulated must have strategy to apply the program, so there is no program which, with the reason not know how to apply. Secondly, all school person that involved with increasing the quality should be given information and told that strategy which is done in increasing the education quality. Third, it is need to form evaluation’s team which involved school organization. To examine the program which has formulated, and the examine result of resources should be communicated to all people in the school.